Contactbased motion graph and its application in locomotion synthesis for virtual actors. (2015) - Wei, Xiaopeng; Yi, Pengfei; Zhang, Qiang
To generate footskate free locomotion along user defined path for virtual actors, a novel data structure of contactbased motion graph is proposed. At first, sample motions are divided to contact clips according to the number of feet in contact with the ground. Then a directed graph can be built by producing nodes and basic edges based on these clips. After generating edges between nodes from different samples by linear interpolation, the contactbased motion graph can be defined as a strongly connected component of this graph. Applying synthesis strategy designed for nodes and edges, a path on contactbased motion graph can be converted to a smooth footskate free motion moving along the given path. The following experiments show the effectiveness of this method.